ULTRASONOGRAPHIC MANIFESTATIONS OF TUBERCULOUS PLEURISY - N. K. Moydunovа; G. T. Turdumаmbetovа; A. S. Kаdyrov (Туберкулез и болезни лёгких)
Goal of the study: to investigate ultrasonographic manifestations of tuberculous pleurisy.Materials and methods. 147 new patients suﬀering from exudative tuberculous pleurisy were examined as well as 90 patients both male and female suﬀering from non-speciﬁc pleural lesions at age from 18 to 65 years old in the out-patient diagnostic department of National Phthisiology Center, Kyrgyzstan Republic. Ultrasonographic manifestations and their intensity were compared in the patients with pleural lesions.Results. The following was conﬁdently more often registered in those suﬀering from tuberculous pleurisy: ﬁbrin deposits on pulmonary pleurae (66.7 ± 3.4%); echogenic suspension, ﬁbrin ﬂakes in pleural ﬂuid (86.3 ± 2.85%); thickness of pleura more than 4 mm (76.3 ± 3.2%); thickness of ﬁbrin deposits more than 4 mm (75.5 ± 3.3%); thick ﬁbrin ﬁbers (80.5 ± 2.2%).